Attentional bias in German Armed Forces veterans with and without posttraumatic stress symptoms – An eye-tracking investigation and group comparison - Küster, Annika; Schumacher, Sarah; Niemeyer, Helen; Engel, Sinha; Spies, Jan; Weiss, Deborah; Muschalla, Beate; Burchert, Sebastian; Tamm, Sascha; Weidmann, Anke; Bohn, Johannes; Willmund, Gert Dieter; et al. (Journal of Behavior Therapy and Experimental Psychiatry, 2022)
Background and objectives Most eye tracking based paradigms evidence patterns of sustained attention on threat coupled with low evidence for vigilance to or avoidance of threat in posttraumatic stress symptoms (PTSS). Still, eye tracking data on attention bias is particularly limited for military population. This eye tracking study investigated attentional bias in PTSS in a sample of German Armed Forces veterans. Methods Veterans with deployment-related PTSS (N = 24), veterans with deployment-related traumatization without PTSS (N = 28), and never-deployed healthy veterans (N = 18) were presented with pairs of combat and neutral pictures, pairs of general threat and neutral pictures, and pairs of emotional and neutral faces. Their eye gazes were tracked during a free viewing task. 3 x 3 x 2 mixed general linear model analyses were conducted. Internal consistency of attention bias indicators was calculated for the entire sample and within groups. Results Veterans with PTSS dwelled longer on general threat AOIs in contrast to non-exposed controls and shorter on general threat and combat associated neutral AOIs in contrast to both control groups. Veterans with PTSS entered faster to general threat AOIs than non-exposed controls. Veterans with PTSS showed circumscribed higher attention fluctuation in contrast to controls. Internal consistency varied across attention bias indicators. Limitations Statistical power was reduced due to recruitment difficulties. Conclusions Evidence is provided for the maintenance hypothesis in PTSS. No robust evidence is provided for hypervigilant behavior in PTSS. Findings on attention bias variability remain unclear, calling for more investigations in this fiel
Keywords: Posttraumatic stress; Eye tracking; Attentional bias; Veterans; Hypervigilance; Maintenance